PEMIKIRAN IGNAZ GOLDZIHER TERHADAP HADIS: (Studi Orientalis Hadis) (Thobaqot: Jurnal Ilmu Hadis, 2024)
Orientalism is a movement or academic study carried out by Western scholars to study the Eastern world, especially Islam. This article will discuss the thoughts of one of the orientalist figures on hadith and sunnah named Ignaz Goldziher. Although Ignaz Goldziher was not the first to criticize hadith, he was highly respected by orientalists and Muslim intellectuals for his significant influence on the development of hadith studies in the West. One of Goldziher's greatest works is a book containing a critical study of the hadith entitled "Muslim Studies Muhammadanische" written in German and consists of two volumes. The main problem in this article is to find out how Ignaz Goldziher thinks about hadith and sunnah. The method used in this paper is a qualitative method with library research, which is to collect data from various scientific works such as books, theses, dissertations, and journals that are relevant to this research. Data sources are collected from two types of sources, namely primary and secondary data sources. Primary sources are obtained from various articles related to Ignaz Goldziher's thought which come from a collection of articles, journals, or thesis that are soft files on the official website. Meanwhile, secondary data sources come from previous literature and research that explain the science of hadith and orientalism. The results of the study show that Ignaz Goldziher's thinking in the field of hadith is related to his doubts about the validity of hadith, whether the hadith comes from the Prophet Muhammad Saw.